Documentary Practice as Praxis: A Direct Appeal to the Realization of the Social Act - Rajchinovska-Pavleska, Natali (Faculty of Media and Communication, 2024)
The essential preoccupation of this paper is documentary practice as (social) praxis, the voice of the photography аs a direct mode of transmission and not only the discovery or mediation of reality. Alan Sekula's photographic discourse is taken as a case study, a practice that directly engages the subject – the position of the worker within the working class, critically representing the reality that is usually masked by spectacle. The hypotheses assume that the methodology of contextualization and discursivization of documentary photography (Untitled Slide Sequence, 1972) leads to a conscious perception of a historical and social reality. Using a cross-methodology of the author's theory and practice, referring to the author's critical point of view, Marxist and post-Marxist theories, this paper indicates that Sekula develops a specific photo-graphology concerned with the directness of expression, the literalness of meaning, and the unmasking of iconic signs captured by capitalist signifiers. The arguments underline that the use of documentary photography as a direct appeal can encourage the realization of a social act. The conclusion implies that the use of the author's voice in the direction of changing the movement of aesthetic production and reception leads to actualization, towards awakening of the passive component – confrontation with social stratification under capitalist order.
Keywords: documentary practice; social praxis; critical position; Allan Sekula; contextualization; discursivization; photo-graphology; realization of the social act